2009
DOI: 10.1002/mnfr.200800165
|View full text |Cite
|
Sign up to set email alerts
|

Chardonnay grape seed procyanidin extract supplementation prevents high‐fat diet‐induced obesity in hamsters by improving adipokine imbalance and oxidative stress markers

Abstract: Studies reported the effects of polyphenols but not for grape polyphenols towards obesity. We analysed the effects of a polyphenolic grape seed extract (GSE) on obesity and oxidative stress in hamsters receiving a high-fat diet (HFD). Three groups of hamsters received a standard diet (STD), or a HFD plus a daily gavage with water (Control, HFD) or a solution of GSE (HFD + GSE) for 12 wk. Plasma glucose, triglycerides (TG), insulin, leptin and adiponectin were measured. Oxidative stress was assessed by cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 49 publications
4
68
1
Order By: Relevance
“…Non flavonoids, highly abundant in grape skin, contain stilbenes such as resveratrol, which is at the basis of the french paradox (Renaud and De Lorgeril, 1992). GSSE has wide-ranging benefits including cardioprotective (Decordé et al, 2009), renoprotective (Safa et al, 2010), and neuroprotective (Wang et al, 2009) effects. GSSE also protects against hepatic ischemia-reperfusion injury (Sehirli et al, 2008), biliary obstruction (Dulundu et al, 2007), and azathioprineinduced hepatotoxicity in rats (El-Ashmawy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Non flavonoids, highly abundant in grape skin, contain stilbenes such as resveratrol, which is at the basis of the french paradox (Renaud and De Lorgeril, 1992). GSSE has wide-ranging benefits including cardioprotective (Decordé et al, 2009), renoprotective (Safa et al, 2010), and neuroprotective (Wang et al, 2009) effects. GSSE also protects against hepatic ischemia-reperfusion injury (Sehirli et al, 2008), biliary obstruction (Dulundu et al, 2007), and azathioprineinduced hepatotoxicity in rats (El-Ashmawy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated the ability of specific botanical compounds to inhibit NADPH oxidase by directly binding to p47 phox (kaempferol) (106), or disrupting the binding of the proline rich region of p22 phox to the tandem SH3 domain of the cytosolic subunits (celastrol) (107). Some polyphenols also have been shown to modulate NADPH oxidase subunit expression (108). Clearly, further studies are necessary to test apocynin (and its metabolites), especially its long-term efficacy, and other NADPH oxidase inhibitors in a variety of animal models of neurodegenerative diseases, and to accumulate additional information about mechanisms of action.…”
Section: Perspectivementioning
confidence: 99%
“…Adiponectin level is also recorded to be lower in type-2 diabetes individuals and CVD patients [44]. It has been demonstrated that chronic consumption of grape phenols resulted in reduction of obesity and related metabolic pathways as well as increased production of adiponectin [45].…”
Section: Dietary Intervention To Reduce Adipose Tissue Inflammation Amentioning
confidence: 98%